New species and new records of Camelobaetidius Demoulin, 1966 (Ephemeroptera: Baetidae) from Southeastern Brazil - Boldrini, R.; Pes, A. M. O.; Francischetti, C. N.; Salles, F. F. (Zootaxa, 2012)
The genus Camelobaetidius Demoulin, 1966 has 37 species distributed throughout the Nearctic and Neotropical Regions, being one of the most studied genera of the family Baetidae. The nymphs are common in lotic habitats, can often be found on top of rocks, and can be easily recognized by the presence of the spatulate tarsal claws. Based on material from Southeastern Brazil, the aim of the present paper is to describe two new species with the terminal filament as long as the cerci (C. juparana sp. nov. and C. spinosus sp. nov.), to describe the female of C. anubis (Traver & Edmunds, 1968), to describe new characters for the male of this species, and to present new records for the genus in southeastern Brazil.